Design and synthesis of novel celastrol derivative and its antitumor activity in hepatoma cells and antiangiogenic activity in zebrafish. Issue 9 (15th February 2019) - Wang, Gang; Xiao, Qi; Wu, Yao; Wei, Ying‐jie; Jing, Yue; Cao, Xiang‐rong; Gong, Zhu‐nan
Abstract: Two series of celastrol derivatives were designed and synthesized by modifying carboxylic acid at the 28th position with amino acid, and their intermediates with isobutyrate at the third position. All compounds were evaluated for their antiproliferation activity by four human cancer cell lines (SCG7901, HGC27, HepG2, and Bel7402) and one normal cell LO2. The most promising compound, compound 8, showed superior bioactivity and lower toxicity than others including celastrol. Further underlying tests illustrated that compound 8 induced apoptosis and cell arrest at G2/M and inhibited proliferation and mobility of human hepatoma cells by suppressing the signal transducer and activator of transcription‐3 signaling pathway. Besides these, a highly accurate and reproducible high performance liquid chromatography protocol was established to determine celastrol and compound 8 absorption in zebrafish, and results demonstrated that their concentration increased rapidly within 4 hr in a time‐dependent manner and the concentration of compound 8 was higher than that of celastrol. In addition, without detection at 12 hr, compound 8 was rapidly metabolized in vivo. These findings are very helpful for the structural modification of celastrol and other bioactive compounds to improve their bioactivity, toxicity, and absorption. Abstract : Collectively, we synthesized celastrol analogues (2–15 ), evaluated their antitumor effects against four cancer cell lines (SGC7901, HGC27, BEL7402, and HepG2) and found compound 8 exhibited excellent antitumor activity. Furthermore, compound 8 could be considered as a JAK2–STAT3 inhibitor of complementing promote apoptosis, inducing metastasis, and blocking the cell cycle with high efficiency and low toxicity. These results support further studies to modify celastrol structure and improve its antitumor activity in future.